2019
DOI: 10.1017/s1368980018004135
|View full text |Cite|
|
Sign up to set email alerts
|

Identifying gaps in the food security safety net: the characteristics and availability of summer nutrition programmes in California, USA

Abstract: ObjectiveThe US Department of Agriculture’s Summer Food Service Program and Seamless Summer Option (summer nutrition programmes (SNP)) aim to relieve food insecurity for children and teens during summer months. More needs to be known about when and where SNP are available, and how availability varies by community characteristics, particularly in rural areas where food insecurity and reduced food access are more prevalent.DesignThe present study examined the geographic availability of SNP and summer meal uptake… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…Although our study is the first to look at the spatial distribution of pandemic school meal site locations in large urban areas during the COVID-19 pandemic, our results could be interpreted in the context of previous work examining meal site placement during school closures. One previous study examined the placement of summer meal sites [ 25 ] and found that urban summer meal sites were more prevalent in larger, higher poverty, and majority non-White high schools. We found similar patterns during the response COVID-19 pandemic, with more sites in the larger, higher poverty and higher minority areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although our study is the first to look at the spatial distribution of pandemic school meal site locations in large urban areas during the COVID-19 pandemic, our results could be interpreted in the context of previous work examining meal site placement during school closures. One previous study examined the placement of summer meal sites [ 25 ] and found that urban summer meal sites were more prevalent in larger, higher poverty, and majority non-White high schools. We found similar patterns during the response COVID-19 pandemic, with more sites in the larger, higher poverty and higher minority areas.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we sought to understand how social and economic resources may be leveraged to facilitate access to school meals for those in greater need, such as provision of financial and logistical support to families [ 34 , 42 ]. High poverty is linked with greater food insecurity [ 25 , 42 ], thus providing greater resources to families may help offset other costs, potentially mitigating the effect of COVID-19 on food insecurity. We recognize that the SSO and SFSP initiatives are developed with the sole purpose to offset food insecurity and thus are grounded following a health equity approach.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…14 This is particularly important when targeting populations with low-income and that identify as racial/ethnic minorities, whose meal participation might be negatively impacted by lack of transportation or child care; public safety concerns including COVID-19; or the chilling effect of the Public Charge Rule, which now makes participating in the USDA Supplemental Nutrition Assistance Program, among other federal social assistance programs grounds for denying a lawful path to citizenship. 15…”
Section: Introductionmentioning
confidence: 99%
“…Another challenge is transportation, particularly in rural areas. 45,46,48,49 Additional barriers include a lack of awareness of site locations among families and a lack of cultural inclusivity. 50 Although implementation strategies have been identified to address these barriers, few have been empirically tested for effectiveness in controlled studies.…”
Section: School-based Child Nutrition Programs Pre-covid-19: a Brief mentioning
confidence: 99%